A Socio-Economical Perspective for a Holistic Management of Temporary Watersheds in Central Mexico Based on a Simple Mathematical Model for Decision-Makers - Gutiérrez-Yurrita, Pedro Joaquín (International Journal of Natural Sciences Research, 2014)
This paper deals with the development of a new holistic math model to manage watersheds in Central Mexico. Hydrological resources in this medium-dry North-American region supply water to more than 49 million people. In addition, this region is considered as one of the most eco-diverse regions in the world. However, the high population density exerts great pressure on water resources in the area, leading to the edge of extinction to most of its biodiversity. Many mathematical models for estimating environmental flows have been developed, yet no model is truly holistic, even integrated, by not taking into account a variable of extreme importance to the ecological functioning of the watershed, its marked seasonal nature (temporality). Due to this lack of information on how to manage temporary rivers, most managers use conventional indices to estimate environmental flows or at best, use the standard Integrated River Basin Management model developed by http://wwf.panda.org/about_our_earth/about_freshwater/rivers/irbm/ [1] though it is only for rivers with permanent flow. The aim of this paper is to present a reflection on the management of temporary flows, presenting a mathematical model that helps decision makers in their operation programs. The holism of the third culture is taken as the paradigm framework to build the model. It should be noted that an important aspect of the model is its simplicity, since it is to be used by people with little knowledge in mathematics and thus easy to take, and common to all the rivers of the region data.